2021
DOI: 10.1021/acsaelm.1c00119
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Conductive Fingerprint Phantoms Made of Ethylene-Vinyl Acetate/Graphene Nanocomposite for Evaluating Smartphone Scanners

Abstract: Fingerprints consist of unique patterns of skin ridges and valleys, and are commonly described by three levels of feature details. Most fingerprint identification systems rely on matching only first- and second-level details; their calibration using unrealistic targets combined with human sampling are cumbersome and time-consuming. We have developed a true-to-life fingerprint phantom with optimized conductive properties and third-level fingerprint details for developing more reliable matching algorithms for po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The portability, powerful computing power, and real-time information integration capability of smartphones greatly facilitate people’s lives. The application of smartphones has widely penetrated into computer science, life science, finance, data science, and other fields. The smartphone’s high-resolution camera, high-efficiency processor and open software platform enable it to perform systematic measurements like professional instruments, especially in colorimetric analysis and image processing. , …”
Section: The Application Of Nanomaterials Combined With Smartphones I...mentioning
confidence: 99%
“…The portability, powerful computing power, and real-time information integration capability of smartphones greatly facilitate people’s lives. The application of smartphones has widely penetrated into computer science, life science, finance, data science, and other fields. The smartphone’s high-resolution camera, high-efficiency processor and open software platform enable it to perform systematic measurements like professional instruments, especially in colorimetric analysis and image processing. , …”
Section: The Application Of Nanomaterials Combined With Smartphones I...mentioning
confidence: 99%
“…Alternatively, spoofs comprised of common household materials such as playdoh, wood glue, or gelatin can be used by a hacker to create an impersonation of a victim's fingerprint. More sophisticated attacks include use of high-resolution 3D [85][86][87] or 2D printing [88], or cadaver fingers [89]. In the domain of face, glasses or a mask could be used for obfuscation, while a replay on a mobile phone could be used for impersonation.…”
Section: Presentation Attacksmentioning
confidence: 99%
“…7 Moreover, level 1 and 2 features are easily forged by molding or inkjet printing methods, making it too difficult for minutiabased fingerprint matching systems to distinguish fake samples from real ones. [8][9][10] In these cases, if level 3 features are adequately utilized in combination with level 1 and 2 features, the error rate of the automated matching system can be reduced by 20%. 6 Moreover, recent studies have indicated that level 3 features can provide additional information about the donor gender, age, race, health, etc.…”
Section: Introductionmentioning
confidence: 99%